The Burden of Burnout Syndrome in Pediatric Intensive Care Unit and Pediatric Emergency Department A Multicenter Evaluation - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Objective The objective of this study was to detect variables associated with burnout syndrome (BS) in pediatric intensive care units (PICUs) and pediatric emergency medicine departments (PEDs) in high-volume centers from different parts of Turkey. Methods An observational, cross-sectional multicenter study was performed. The Maslach Burnout Inventory scale was administered to all of health care providers working in PICUs and PEDs. In this study, health care providers were defined as physicians, nurses, and other staff (secretaries, cleaning and patient care staff) working in PICU and PEDs. Results A total of 570 participants completed the survey. The major finding of this study was that 76.1% (n = 434) of PICU and PED health care professionals had BS. The most prominent subscale of BS was emotional exhaustion (62.5%). The rate of BS was higher among health care providers working in PEDs compared with PICUs (79.1% vs 73.7%, P = 0.04). The frequency of BS according to emotional exhaustion and depersonalization subscales was higher in health care providers of PEDs. The rate of BS was also significantly higher in younger employees, females, those working 51 or more hours totally in a week, those having a low monthly salary, those single or divorced, those without children, those with no childcare at home, those not owning a home, those not doing regular exercise and not having regular breakfast, those with total employment time of less than 1 year, and those not having a car or not having a hobby. In PEDs, when the daily evaluated number of patients was equal to or more than 44 (sensitivity, 88%; specificity, 66%), it predicted the occurrence of BS. In PICUs, when the number of patients cared for by 1 nurse was equal to or more than 3, it predicted the occurrence of BS (sensitivity, 78%; specificity, 62%). Conclusions By creating early intervention programs to prevent BS, shortages of health care professionals can be avoided and the costs of health care expenditures related to infections can be decreased.
Keywords: burnout syndrome; pediatric intensive care unit; health care providers; PREVALENCE